Highly Transparent Organic Solar Cells with All‐Near‐Infrared Photoactive Materials. Issue 12 (25th July 2019) - Xie, Yuanpeng; Xia, Ruoxi; Li, Tengfei; Ye, Linglong; Zhan, Xiaowei; Yip, Hin‐Lap; Sun, Yanming
Abstract: Transparent organic photovoltaics are identified as important components for building‐integrated photovoltaics and smart window technologies. In this work, highly transparent organic solar cells (T‐OSCs) based on all‐near‐infrared (NIR) harvesting materials (optical bandgap, E g opt < 1.4 eV) are first fabricated. Both donor and acceptor materials used in T‐OSCs exhibit great transparency in the visible region. After combining MoO3 /Ag or MoO3 /Ag/MoO3 transparent electrode, T‐OSCs show excellent visible light transmittance (VLT) of 52–61.5% with power conversion efficiencies of 3.5–4.2%. As far as it is known, this all‐NIR active layer represents the most visible transparent donor–acceptor combination in OSCs. In addition to high VLT, T‐OSCs have great aesthetic value, good color‐rendering index (CRI > 90), and high light energy utilization properties. This work highlights great potential of NIR photoactive materials for T‐OSCs. Abstract : All‐near‐infrared transparent organic solar cells (T‐OSCs) are fabricated using a new method involving two ultranarrow bandgap ( E g opt < 1.4 eV) photoactive materials. The T‐OSC yields an outstanding visible light transmittance of 61.5% with an efficiency of 3.5%, indicating great potential of all‐NIR materials in high‐quality T‐OSCs.